The attitude of Moscow youth to the topic of patriotism in domestic cinema - O. A. Kulikova; A. S. Ryabovicheva (Вестник университета)
The article is devoted to the theme of patriotism in Russian films from different time periods. The authors point out that such films are being created in order to foster love and respect for the Motherland; however, there is an emerging problem of a decline in the popularity of domestic films on such topics and that of the lack of interest in the topics among young people. The contradiction lies in the fact that such films are becoming increasingly relevant, mainly due to the overall political situation and changes in Russian film distribution. Meanwhile, there is a lot of talk about the quality of domestic patriotic films. Questions are being raised as to which films are of higher quality, what ideas should be popularized among the population, whether such movies really evoke a sense of pride in the Motherland or only ridicule, and whether they are effective in the framework of patriotic education programs. To assess the current situation, the authors of the article collected and analyzed youth representatives’ opinions on the topic of patriotism in domestic cinema. The results of the study allow to form an idea of how works of cinematic art can be used for educating citizens and moving the culture forward.